The Impact Of Corporate Social Responsibility And Corporate Governance On Corporate Reputation: The Interaction Effect Of National Culture From Mena Countries - A, Eriqat Ibrahim O (2023)
Corporate reputation is a valuable intangible asset that plays an important role in developing a strong corporate competitive advantage. It is a logical outcome of effective corporate governance and corporate social responsibility initiatives, as they can act as signals that affect stakeholders‘ perceptions and expectations regarding the company‘s future behavior. However, stakeholders‘ interests, expectations, and perceptions may be influenced by other factors, such as national culture, which forms their beliefs about the role companies should play in society. Therefore, the objective of this study is to investigate the influence of CSR and corporate governance on corporate reputation, while considering the interaction effect of national culture on the relationship between CSR and corporate reputation. The study examines a sample of 96 financial companies listed on the stock exchanges of four MENA countries: Jordan, Palestine, Qatar, and Kuwait, during the period from 2016 to 2020. To develop corporate reputation index, the study employs Principal Components Analysis (PCA) as a technique for multivariate analysis. Furthermore, the study applies the dynamic panel system Generalized Method of Moments (GMM) to estimate the dynamic corporate reputation models. The findings of the study indicate that CSR has a significant positive impact on corporate reputation, implying that CSR improves corporate reputation